Optimizing Digital Technology and Institutional Reform to Elevate the International Reputation of Universities in Indonesia and Malaysia - Irawaty Irawaty; Dani Muhtada; Dina Silvia Puteri; Roziya Abu; Ayup Suran Ningsih (Journal of Law and Legal Reform, 2025)
Indonesian universities are increasingly expected to enhance their international reputation, particularly in comparison to Malaysian institutions, which have achieved higher global rankings. Key indicators of international recognition include publications, citations, and research. This study aims to compare the use of digital media by universities in Indonesia and Malaysia in supporting these indicators. The research will address three main questions: the role of government regulations and facilities in both countries in shaping university reputation, how universities utilize their official websites or portals, and the similarities and differences in digital strategies. A qualitative comparative approach will be applied, using primary data from regulations and university portals, along with secondary sources such as interviews, literature, and media. Relevant regulations include Indonesia’s Higher Education Law and Malaysia’s Education Act 1996. This study focuses on the digital presence of Universitas Negeri Semarang (Indonesia) and Universiti Teknologi MARA (UiTM) Malaysia. While both institutions utilize digital platforms, UiTM has shown more advancements in e-learning and digitizing administrative processes. In contrast, Universitas Negeri Semarang continues to improve its digital content to enhance accessibility and interactivity. By analyzing these approaches, this study seeks to highlight best practices and areas for improvement, ultimately contributing to the broader effort of strengthening Indonesian universities’ global standing.